Morphology and phylogenetic position of three species of genus Camptocercus Baird, 1843 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zootaxa, 2015)
Morphology of three species of the cladoceran genus Camptocercus Baird, 1843 (Anomopoda: Chydoridae), North Asian C. streletskayae Smirnov, 1998, Australian C. australis Sars, 1896 and Neotropical C. dadayi Stingelin, 1913, is investigated. Revealed data confirm a high level of morphological diversity within the genus. C. australis and C. dadayi belong to the uncinatus-clade of the genus, while C. streletsakayae is an advanced species with unclear phylogenetic position within the genus.